Integrating Design Thinking and Agile Scrum Methodology In Human Resources Management System Development: Digital Transformation In Employee Management Case Study on PT Derma Konsep Estetika - Fahri Fauzan; A A B Dinariyana (Dinasti Publisher, 2024)
In the current digital era, efficiency in human resource management (HRM) is a crucial key to the operational success of companies. This research focuses on the development of a Human Resource Management System (HRMS) application product aimed at enhancing efficiency in managing employees by digitizing critical processes such as leave requests, overtime, monthly attendance recapitulation, employment contracts, payroll information, employee personal data, employee special records, and company activity announcements. The previously manual and traditional approach has been transformed into a systematic and digital one through the application of HRMS technology. This application is designed using the Design Thinking methodology to ensure that the solutions developed are truly user-centered, by deeply understanding user needs and creating innovative and user-friendly solutions. The application development is carried out using the Agile Scrum methodology, which allows the development team to work iteratively and adaptively, ensuring flexibility in development and the ability to quickly respond to rapidly changing user needs. The results of this study demonstrate that the implementation of Design Thinking and Agile Scrum can effectively achieve digital transformation in employee management. The developed HRMS application showcases how these methodologies can revolutionize HR processes by addressing challenges and improving overall efficiency. By leveraging digital technology, the study highlights the potential for substantial improvements in managing employee administration, thereby fostering a more organized and efficient HR management system.